"Contrasting features of tropospheric turbulence over the Indian peninsula". (January 2020) - Muhsin, M.; Sunilkumar, S.V.; Ratnam, M. Venkat; Parameswaran, K.; Mohankumar, K.; Mahadevan, S.; Murugadass, K.; Muraleedharan, P.M.; Kumar, B. Suneel; Nagendra, N.; Emmanuel, Maria; Chandran, P.R.Satheesh; et al.
Abstract: Altitude structure of turbulence in the troposphere and lower stratosphere (TLS) over the Indian peninsula is delineated using radiosonde observations carried out from six stations (August 2013 to December 2017) as part of the Tropical Tropopause Dynamics (TTD) Campaign under the GPS Aided Radiosonde Network Experiment for Troposphere–stratosphere Studies (GARNETS) program. Thorpe analysis applied to the potential temperature profiles, taking into account the impact of atmospheric moisture and instrumental noise, is used to estimate the turbulence parameters. This study shows that while the occurrence of turbulence is high in the lower (0–2 km) and upper (10–15 km) troposphere, the region 3–8 km is relatively devoid of turbulence at all the six stations. In general, ~60% of the Thorpe scale (LT ) values in the troposphere are less than 250 m at all the stations, except at Cochin where it extends up to 400 m. Though the altitudinal structure of turbulence shows large variability from station-to-station, it does not show any systematic latitudinal pattern. This study also shows that the Thorpe method appears to be good in identifying convectively induced turbulence than the dynamically (shear) induced turbulence. In the lower troposphere, the turbulence is due to both convective and dynamic instability at all the stations. While turbulence in the altitude region between 10 and 15 km is mainly due to convective instability at Coimbatore, Gadanki and Goa and due to dynamic instability at Cochin, both these instabilities contribute significantly to the generation of turbulence at Trivandrum and Hyderabad. Occurrence of convective instability (turbulence) under clear-air conditions in the upper troposphere, suggests wave breaking as a mechanism. Highlights: Altitude structure of turbulence studied over six locations of Indian peninsula. Occurrence of turbulence is high in the lower and upper troposphere. There is no systematic station to station variations in the turbulent structure. Convective and dynamical instabilities are responsible for the turbulence generation. Thorpe method appears to be good in identifying convectively induced turbulence.